ANALISIS MARGIN OF SAFETY USAHA PETERNAKAN PUYUH â€œMERRYLANDâ€ DI DESA KALI KECAMATAN PINELENG KABUPATN MINAHASA - Wangefela, Lisa; Santa, N M; Salendu, A H.S; Kalangi, L S (Universitas Sam Ratulangi, 2018)
ABSTRACTÂ ANALYSIS OF SAFETYÂ MARGIN ON â€œMERRYLANDâ€ QUAIL POULTRY FARM AT KALI VILLAGE PINELENG DISTRICT OF MINAHASA REGENCY.Â The purpose of this study was to determine the break-even point of